New seismological constraints on differential rotation of the inner core from Novaya Zemlya events recorded at DRV, Antarctica - Souriau, Annie (Geophysical Journal International, 1998)
Novaya Zemlya nuclear test records at the seismic station DRV, Antarctica, are analysed in order to obtain further constraints on a possible differential rotation of the inner core with respect to the mantle. These data allow the sampling of the inner core along a nearly polar path in very stable conditions over more than two decades, from 1966 to 1990. The PKP (BC)– PKP (DF) traveltime residuals, which reflect the inner-core anisotropy and/or heterogeneities sampled along the path, exhibit a great stability through time. A computation of the residuals that are expected for various differential rotation rates and the same rotation axis as the mantle has been performed using the worldwide residual catalogue of Engdahl et al . (1997) for summary rays that include the time as an additional parameter in data stacking. Comparison of data and predictions shows that an eastward differential rotation with a rate as large as 3°yr−1, as suggested by some authors, is not possible, but an eastward rotation at 1°yr−1 or lower cannot be rejected.